GAME EDUKASI MATEMATIKA “Tang Mane Bakoel Saprahan” DENGAN KONTEKS KEARIFAN LOKAL MELAYU KALIMANTAN BARAT - Riyanti Nurdiana; Siti Nur Asmah (JPMI (Jurnal Pendidikan Matematika Indonesia), 2022)
This study aims to activate students activities by playing while learning, reducing the use of gadgets by increasing physical activity and making it easier for students to understand the coordinate material system with the language and culture in their area. The research method used is the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The results showed that the mathematics education game "Tang Mane Bakoel Saprahan" with the context of West Kalimantan Malay Local Wisdom was feasible, practical and effective to be used in the learning process. This game is very interesting for students and makes it easier for students to learn mathematics through games and can make one of the teacher's methods in delivering learning material through the media also does not occur simultaneously with local culture.